Sosialisasi Dan Pendampingan Pembuatan Nomor Induk Berusaha (NIB) Di Desa Santong Kecamatan Kayangan Kabupaten Lombok Utara - Bagus Dwi Hari Setyono; Baiq Dinda Inges Mutiara Hati; Nova Aji Saputra; Neli Agustina (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Santong Village has abundant plantation and agricultural products such as cloves, bananas, and coffee. So, it is not surprising that in Santong Village there are many business actors or MSMEs (Micro, Small and Medium Units) banana sale, coffee or other businesses. The large number of business actors and MSMEs in Santong Village who do not yet have a NIB business license (Business Identification Number) makes the University of Mataram (Unram) Thematic KKN 2022 in collaboration with the North Lombok Regency Investment and Business Social Service, The Sheep Indonesia Foundation, and Santong Village-Owned Enterprises (BUMDes) to hold socialization activities and make NIB for business actors and MSMEs in Santong Village. The purpose of holding this socialization activity is so that business actors and MSMEs in Santong Village understand the importance of having a NIB business license. The method of socialization uses means; First, students of the 2022 Santong Village Unram Thematic KKN held a discussion with the Sheep Indonesia foundation regarding the implementation of socialization and making NIB for business actors and MSMEs in Santong Village who do not yet have NIB. Second, students of the 2022 Santong Village Unram Thematic KKN notify and disseminate information about the implementation of socialization and making NIB to all business actors and MSMEs who do not yet have a NIB business license and are in Santong Village. Third, the Unram Thematic KKN together with the North Lombok District investment and business social service, the Sheep Indonesia Foundation, and Santong BUMDes carried out socialization on the importance of having NIB for business actors and MSMEs. Fourth, Unram Thematic KKN helps the process of making emails for business actors and MSMEs who do not have an active email so that later when the process of making a NIB business license runs smoothly. Fifth, the social office of investment and business along with the Unram Thematic KKN made the NIB and immediately distributed the NIB business license in sheet form after the NIB manufacturing process was successful. It is hoped that with the socialization and creation of NIB by the Unram Thematic KKN Santong Village 2022 can provide awareness of the importance of having a NIB business license for business actors or MSMEs who want to run their business.